ICT capacities for teachers of intermediate, trade schools and colleges: An urgent problem - Nguyen, Toàn (Journal of Technical Education Science, 2009)
The use of ICT in education today is no longer a luxury reserved to some teachers who are also experts in this field. It has become an indispensable tool for an efficient teaching and learning. Actually, however, the use of ICT in teaching at colleges, intermediate and trade schools is still very limited, non - standardized and unpopular. The Department of Education and Training itself has not developed an ICT strategy yet, while a comprehensive orientation and policy at national level is still inexistent. This article briefly describes several principal uses of ICT in education and some fundamental norms to be kept in using ICT tools and attempts to give some suggestions for possible solutions to such an urgent problem.